Understanding Service-Oriented Architecture (SOA): A systematic literature review and directions for further investigation. (July 2020) - Niknejad, Naghmeh; Ismail, Waidah; Ghani, Imran; Nazari, Behzad; Bahari, Mahadi; Hussin, Ab Razak Bin Che
Abstract: Service-Oriented Architecture (SOA) has emerged as an architectural approach that enhances the service delivery performance of existing traditional systems while still retaining their most important features. This approach, due to its flexibility of adoption, has gained the attention of both academic and business entities, especially in the development of world-leading technologies such as Cloud Computing (CC) and the Internet of Things (IoT). Although many studies have listed the success factors of SOA, a few minor failures have also been reported in the literature. Despite the availability of rich material on SOA, there is a lack of systematic reviews covering the different aspects of the SOA concept in Information Systems (IS) research. Therefore, the central objective of this study is to review existing issues of SOA and share the findings with the academia. Hence, a systematic literature review (SLR) was conducted to analyse existing studies related to SOA and the factors that led to SOA success and failure from 2009 to 2019. To completely cover all SOA-related research in the IS field, a two-stage review protocol that included automatic and manual searching was applied, resulting in 103 primary studies. The articles were categorised into four research themes, namely: SOA Adoption, SOA Concepts, SOA Impact, and SOA Practice. The result shows that the academic research interest on SOA increased recently with most of the articles covering SOA Practice followed by SOA Adoption. Moreover, the findings of this review highlighted SOA Governance, SOA Strategy, Financial Issues and Costs, and Education and Training as the most significant factors of SOA adoption and implementation. Consequently, the outcomes will assist professionals and experts in organisations as well as academic researchers to focus more on these factors for successfully adopting and implementing SOA. Highlights: This systematic study reviewed a large scale of literature to determine the current state of SOA research, resulting in 103 primary studies. This review highlighted SOA Governance, SOA Strategy, Financial Issues and Costs, and Education and Training as the most significant factors of SOA adoption and implementation. Four research themes obtained from the primary studies, namely, SOA Adoption, SOA Concept, SOA Impact, and SOA Practice. This study comes up with a mind map of SOA themes, relevant topics, and methodologies.